PENINGKATAN PEMAHAMAN MODUL PENGANTAR STATISTIKA MELALUI DISKUSI EKSPLORATIF YANG MENEKANKAN PENGETAHUAN METAKOGNITIF PADA MAHASISWA S1 PGSD POKJAR SIDOARJO - Prastiti, Tri Dyah; Mairing, Jackson Pasini (Jurnal Pendidikan, 2011)
Recently, the phenomenon of the tutorial activities in mathematics class shown that the tutee still passive and just tended to accept tutor explanations. It made mathematics was considered as a difficult subject. Based on this reason, the authors conducted research on tutorial focused to improvement the studentsabilities in Pengantar Statistika I dan II by using explorative discussion that emphasizes on the metacognitive knowledge level. The subjects are S1-PGSD students at second semester in Sidoarjo. The research is conducted in two cycles and shown that the use of the explorative discussion method that emphasizes on the metacognitive knowledge level is able to increase of the students understanding and independence.